2019
DOI: 10.1055/s-0039-1700187
|View full text |Cite
|
Sign up to set email alerts
|

Relational Model between Parental Dental Belief and Formation of Dental Fear among Preschool Children in Indonesia

Abstract: Objective Parents’ behavior and belief can strongly impact preschool children. Parents play an important role in the formation of dental fear. The aim of the research is to analyze parental dental belief model as a source of dental fear among preschool children. Materials and Methods The research was undertaken at 15 kindergartens in Bandung City, Indonesia, which were chosen by means of multistage cluster random sampling. The participants of the research were parents and children aged 3 to 6. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…5,11,33 As mentioned previously in our results, when responding to MDAS, 42% of the participants were slightly anxious and 29.4% were very anxious about dental anesthesia, in line with the findings of Gaffar et al 11 Surprisingly, although in the current study, the level of dental anxiety also varied between different dental procedures, but these changes were not statistically significant (p ¼ 0.52), contradicting the findings of a clinical trial on 50 patients, which found that extractions (p ¼ 0 0.017) and local anesthesia injections (p ¼ 0.013) caused a tolerable rise in the systolic blood pressure. 29 Many factors that vary among individuals such as age, education, and socioeconomic and dental beliefs may lead to different reactions which, in turn, contribute to the formation dental anxiety 34 .…”
Section: Discussionmentioning
confidence: 99%
“…5,11,33 As mentioned previously in our results, when responding to MDAS, 42% of the participants were slightly anxious and 29.4% were very anxious about dental anesthesia, in line with the findings of Gaffar et al 11 Surprisingly, although in the current study, the level of dental anxiety also varied between different dental procedures, but these changes were not statistically significant (p ¼ 0.52), contradicting the findings of a clinical trial on 50 patients, which found that extractions (p ¼ 0 0.017) and local anesthesia injections (p ¼ 0.013) caused a tolerable rise in the systolic blood pressure. 29 Many factors that vary among individuals such as age, education, and socioeconomic and dental beliefs may lead to different reactions which, in turn, contribute to the formation dental anxiety 34 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Children's DFA is a dynamic process that depends on many different factors, such as age, gender, maternal dental fear, unbearable pain during the first dental visit, and even the sweet consumption frequency. 2,3 With that, the associations of DFA prevalence with age and sex are not almost clear. It is considered that younger children and girls have higher odds of displaying negative behavior, and that girls usually have higher rates of severe dental fear than boys.…”
Section: Introductionmentioning
confidence: 99%
“…Behavior and attitudes can be in the form of knowledge accompanied by a tendency to act according to knowledge. 4,[14][15][16][17] The role of parenting on the oral health of their children is divided into two aspects. The first aspect is the role of parents in determining diet patterns, brushing teeth, and using fluoride-containing toothpaste in children.…”
Section: Discussionmentioning
confidence: 99%